2018
DOI: 10.1186/s12964-018-0295-1
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 inhibition promotes breast cancer metastasis through EGFR-mediated β-catenin nuclear accumulation

Abstract: BackgroundKnockdown of Akt1 promotes Epithelial-to-Mesenchymal Transition in breast cancer cells. However, the mechanisms are not completely understood.MethodsWestern blotting, immunofluorescence, luciferase assay, real time PCR, ELISA and Matrigel invasion assay were used to investigate how Akt1 inhibition promotes breast cancer cell invasion in vitro. Mouse model of lung metastasis was used to measure in vivo efficacy of Akt inhibitor MK2206 and its combination with Gefitinib.ResultsKnockdown of Akt1 stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 52 publications
1
42
0
1
Order By: Relevance
“…EGFR activation usually initiates β‐catenin nuclear accumulation in tumor development (Yang et al, ; Ji et al, ). AKT inhibition increases EGFR activation through a negative feedback loop in breast cancer cells (Er et al, ; Li et al, ). Since PI3K is one of the dominant upstream molecules of Akt signaling (Lee et al, ), therefore, we speculated that PI3K inhibitor LY294002‐induced β‐catenin nuclear accumulation is dependent upon the activation of EGFR in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR activation usually initiates β‐catenin nuclear accumulation in tumor development (Yang et al, ; Ji et al, ). AKT inhibition increases EGFR activation through a negative feedback loop in breast cancer cells (Er et al, ; Li et al, ). Since PI3K is one of the dominant upstream molecules of Akt signaling (Lee et al, ), therefore, we speculated that PI3K inhibitor LY294002‐induced β‐catenin nuclear accumulation is dependent upon the activation of EGFR in breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) overexpression in breast cancer is known to be associated with proliferation, survival, and migration of cancer cells (Wee and Wang, 2017;Li et al, 2018;Sigismund et al, 2018). Several studies suggested that breast cancer cells confer resistance to PI3K Cell Biol Int 43 (2019) 931-939 © 2019 International Federation for Cell Biology inhibitors by reactivating EGFR signaling pathways through a negative feedback loop (Stratikopoulos et al, 2015;Timmermans-Sprang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We could prove the suppression of AKT1 by miR-373-3p in ECa cell lines. AKT1 was an oncogene in several cancer diseases including osteosarcoma, pancreatic ductal adenocarcinoma, colorectal cancer, and breast cancer [32][33][34][35] .Recently, lncRNAs have been implicated in the miRNA/AKT1 axis modulation in www.nature.com/scientificreports/ human cancers. For instance, the LINC00324 counteract miR-615-5p and enhance the expression of AKT1 in lung adenocarcinoma 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was conducted as previously described [16]. Briefly, the total proteins were extracted from left ventricles using ice-chilled RIPA lysis buffer containing 50 mM Tris-HCl (pH 8.0), 150 mM NaCl, 0.5% sodium deoxycholate, 0.1% SDS, 1% NP-40, 5 mM EDTA, 0.25 mM PMSF, and protease inhibitor cocktail.…”
Section: Western Blotmentioning
confidence: 99%